Humour and gender hegemony: the panoptical role of ridicule vis-à-vis gender - Abedinifard, Mostafa (My University, 2015)
My dissertation addressed the policing role of ridicule, as a form of humor, in relation to gender norms. Using cultural studies methods and drawing on theories in humor studies and gender—particularly masculinities—studies, I examined various forms and instances of mainstream gender humor from both Iranian and US cultures; I argued that such humor reflects and, through ridicule’s punitive role, systematically reinforces hegemonic notions of gender in a society. I concluded that the role of ridicule in the construction of gender demands theoretical and practical attention in studies of gender relations.
Keywords: gender humour; gender studies; ridicule